Vilas operárias: centros de ordem e exclusão na vila operária de Camaragibe - PE (1900-1929) - Santos, Marcos Alesandro Neves dos (2017)
This work aims to analyze the Camaragibe workers” village, located in the metropolitan region of Recife and established at the beginning of the 2oth century, more precisely from 1900 until 1929, focusing on the attempt of ordering and exclusion over a workerºs life. To do so, a re-reading of the historiography related to the aforementioned period was performed, based on newspapers of the time and internal documents of the Camaragibe Factory, which enabled a better understanding of how the formation of the "ideal worker" was structured. Workers” villages, in the late l9th and early ZOth centuries, represented the ideal housing, being seen as the opposite of the proletarian habitation, which, in the so-called official discourse, was the irradiating focus of disease and "had habits." The capital of Pernambuco, like so many other state capitals in Brazil, did not have a good physical infrastructure: it was an environment with precarious basic sanitation and a poor lighting system, which resulted in living conditions considered unhealthy. Such a conjuncture represented, for the elite, a risk to the working class, insofar as removing it from the urban milieu and moralizing it was, besides a social measure, a main attempt to control over a class considered to be a potential dangerous", though indispensable to the gearing of the capitalist system.